Particulate matter emission factors for biomass combustion - Amaral, Simone Simões [UNESP]; de Carvalho, João Andrade [UNESP]; Costa, Maria Angélica Martins [UNESP]; Pinheiro, Cleverson (MDPI, 2016)
Emission factor is a relative measure and can be used to estimate emissions from multiple sources of air pollution. For this reason, data from literature on particulate matter emission factors from different types of biomass were evaluated in this paper. Initially, the main sources of particles were described, as well as relevant concepts associated with particle measurements. In addition, articles about particle emissions were classified and described in relation to the sampling environment (open or closed) and type of burned biomass (agricultural, garden, forest, and dung). Based on this analysis, a set of emission factors was presented and discussed. Important observations were made about the main emission sources of particulate matter. Combustion of compacted biomass resulted in lower particulate emission factors. PM2.5 emissions were predominant in the burning of forest biomass. Emission factors were more elevated in laboratory burning, followed by burns in the field, residences and combustors..
Keywords: Air pollution; Biomass burning; Emission factor; Particulate matter